2020
DOI: 10.1042/cs20201233
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-regulated aminopeptidase deficiency impairs cardiovascular adaptations and placental development during pregnancy

Abstract: Insulin-regulated aminopeptidase (IRAP), an enzyme that cleaves vasoactive peptides including oxytocin and vasopressin, is suggested to play a role in pregnancy and the onset of preeclampsia. Our aim was to examine the contribution of IRAP to arterial pressure regulation and placental development during pregnancy in mice. Mean arterial pressure and heart rate were measured via radiotelemetry in 12-week-old female wildtype and IRAP knockout mice. Females were time-mated with males of the same genotype. Placenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Ang IV may have effects on the renal vasculature and renal blood flow that are biphasic with the vasoconstrictor and pressor responses being mediated through AT 1 R while the prolonged vasodilator activity being through IRAP [ 99 ]. IRAP knockout mice do not have altered blood pressure, but do have increased vasopressin sensitivity during pregnancy [ 53 ]. However, we have reported that Ang III increases renal sodium excretion by inhibiting luminal NHE3 and basolateral Na + /K + -ATPase activity in Wistar-Kyoto but not spontaneously hypertensive rats [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ang IV may have effects on the renal vasculature and renal blood flow that are biphasic with the vasoconstrictor and pressor responses being mediated through AT 1 R while the prolonged vasodilator activity being through IRAP [ 99 ]. IRAP knockout mice do not have altered blood pressure, but do have increased vasopressin sensitivity during pregnancy [ 53 ]. However, we have reported that Ang III increases renal sodium excretion by inhibiting luminal NHE3 and basolateral Na + /K + -ATPase activity in Wistar-Kyoto but not spontaneously hypertensive rats [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, nanomolar concentrations of Ang IV have been reported to increase BP in rats by interacting with the AT 1 R [ 48 ]. Some effects of Ang IV in the kidney may be through the binding and inhibition of insulin-regulated aminopeptidase (IRAP) activity [ 52 ]; global IRAP knockout mice have increased vasopressin sensitivity, yet no change in blood pressure [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…The AT4R is highly expressed in the heart, skeletal muscles, kidneys, small intestine, placenta and blood vessels and alternative splicings result in multiple transcript variants encoding different isoforms. Interestingly, placental AT4R is upregulated during early pregnancy implicating its role in the migration of extravillous trophoblasts (EVT) ( 55 ).…”
Section: Erap1 Erap2 and Irap In The Renin-angiotensin Systemmentioning
confidence: 99%